Circulation patterns identified by spatial rainfall and ocean wave fields in Southern Africa - Bárdossy, András; Pegram, Geoffrey; Sinclair, Scott; Pringle, Justin; Stretch, Derek (Frontiers in Environmental Science, 2015)
This paper presents the applications of Fuzzy Rule Based Circulation Patterns (CPs) classification in the description and modelling of two different physical consequences of their form: Rainfall regimes and Wind generated Ocean Waves. The choice of the CP groupings is made by searching for those CPs which generate (i) different daily rainfall patterns over mesoscale regions and (ii) wave directions and heights at chosen shoreline locations. The method used to choose the groupings of CPs is a bottom-up methodology using simulated annealing, ensuring that the causative CPs are responsible for the character of the results. This approach is in marked distinction to the top-down approaches such as k-means clustering or Self Organising Maps (SOMS) to identify several classes of CPs and then finding the effects of those CPs on the variables of choice on given historical days. The CP groups we define are quite different for the two phenomena rainfall and waves, simply because different details of the pressure fields are responsible for wind and for precipitation. Large ocean waves are typically generated over fetches of the order of thousands of kilometres far off shore, whereas rainfall is generated by local atmospheric variables including temperature, humidity, wind speed and radiation over the area of concern. The spatial representativeness of the CPs is discussed and classifications obtained for different regions are compared. The paper gives examples of applications of the ideas over South Africa.